Land Bank Agency in The Implementation of Land Acquisition for the Public Interest in Indonesia - Irman Syahriar; Benhard Kurniawan Pasaribu; Dina Paramitha Hefni Putri; Khairunnisah Khairunnisah (International Journal Labs, 2022)
Background: Land acquisition is a way to acquire land for development for the public good. Article 18 of the Agrarian Constitution number 5 of 1960 states that: